DAMPAK PENERAPAN SERVANT LEADERSHIP DI INSTITUSI PENDIDIKAN TINGGI: SEBUAH TINJAUAN LITERATUR - Andriansyah, Edi (Journal of Management and Innovation Entrepreneurship (JMIE), 2024)
This literature review examines the impact of servant leadership implementation in higher education institutions. Through a synthesis of existing research, it identifies the benefits, challenges, and outcomes associated with servant leadership practices in academia. The review highlights how servant leadership fosters collaboration, empowerment, and trust among faculty, staff, and students, leading to improved communication, engagement, motivation, and community within institutions. It also underscores the positive correlation between servant leadership behaviors and employee engagement, job satisfaction, and organizational commitment. Additionally, the review emphasizes the impact of servant leadership on student learning outcomes, including academic achievement, engagement, retention, and satisfaction. Scholars are increasingly focusing on developing servant leadership competencies among academic administrators and faculty and conducting longitudinal studies to assess long-term effects and best practices. Overall, the findings underscore the significant impact of servant leadership on higher education quality and organizational success, emphasizing the need to integrate servant leadership principles into leadership practices within higher education institutions. Further research in this area can provide deeper insights into effective servant leadership practices and their practical implications in higher education.